Substitution of cotton-seed meal and soybean meal for soybean hay made from mature soybean plants, in the nutrition of dairy cows - Durães, Marcus Cordeiro; Emrich, Edywald Soeiro; Souza, Júlio César de; Castro, Celso Soares de; Batista, João Soares (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted at Sete Lagoas, Minas Gerais, Brazil, to compare the use of soybean hay made from mature soybean plants (Glycine max (L.) Merril) with cotton-seed meal and soybean meal, in relation to the nutrition of dairy cows. Twelve cows were fed a basic diet of corn silage supplemented with cotton-seed meal in ration A, soybean meal in ration B, and mature soybean hay in ration C. The three rations were equivalent from the point of view of milk production and percentage milk protein. However, ration B caused a significant (P < 0,05) reduction in the percentage milk fat in relation to the other rations. Analysis showed that ration A was the least profitable economically.